Formulation and Evaluation of Furosemide Solid Self-emulsifying Drug Delivery System - Renuka, J. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of the present study was to develop a novel solid self-emulsifying drug delivery system (SEDDS) to enhance the solubility, dissolution rate and ultimately the oral bioavailability of a poorly water-soluble drug, and furosemide. Materials and Methods: Phase solubility studies were conducted using various oils (oleic acid, and soybean oil, sunflower oil, surfactants Tween20, and Cremophor RH 40) and cosolvent (ethanol) for the maximum solubility of furosemide. Ternary phase diagrams were constructed to evaluate the self-emulsification domains and were also for the optimum concentrations of oil and surfactants in the formulation. The globule size analysis, polydispersity and zeta potential of all the developed formulations were studied using Malvern Zetasizer. In vitro release studies and emulsification time were conducted using USP Type II dissolution test apparatus. Statistical Analysis: Fourier transform infrared (FTIR) analysis for investigating the drug excipients interactions and scanning electron microscopy studies for the size, shape, and morphology of the globules after the emulsification process was performed. The formulation of furosemide SEDDS was compared with commercial tablets (LasixÂ® 40). Results: The results of the studies indicated that the rate of dissolution of the developed SEDDS formulations containing furosemide was 2.9â€“3.6 folds increased compared with that of commercial tablets. The mean globule size (n = 3) was observed to be below 100 nm for the optimized formulations, and the zeta potential was negative which may not interfere in the absorption of the formulation. There were no interactions between the drug, oil, and surfactants, which were confirmed from the results of FTIR studies. Conclusion: The developed SEDDS formulation improved the solubility and in vitro drug release of furosemide when compares with commercial tablet formulation.